Bundle Mega Enterprise / Muhammad Amirul Izham Mohd Nawawi ... [et al.] - Mohd Nawawi, Muhammad Amirul Izham; Kodir, Nur Hidayah; Nik Leh, Nik Nur Aini; Rejab, Shahkirah; Wan Mazlan, Wan Nur Anis Hazwani (2021)
Ongoing attempts to achieve more resource-efficient production and consumption, as well as reuse, have a high potential to aid development toward systems based on circular economy thinking. To accomplish this goal, the motivations, means, and opportunities for reuse must be recognised so that best practises may be discovered and decision-making can be made more effective as a result. Malaysia's mainstream increase in "bundle" clothes consumption matches the global trend of thrift shopping. Theories surrounding this phenomena span from the emergence of recessionist as to environmental conservation and identity building. Nowadays, we can observe a trend of bundling, or diving into clothes bundles at thrift stores, particularly bundle mega, when people purposefully buy tangible things in order to convey their fashion choices to the general public This phenomena is also explained using Bourdieu's notions of habitus and field. This is a hypothesis that the act of thrift shopping or bundling here is not solely due to a lack of finances based on social class, as people of all income levels participate in this activity. Rather, purchasing bundle clothing is an act of building one's "street cred" or social capital, with the more unusual the find, the more "street cred" one earns. This is also a popular hobby among the hipster subculture. Furthermore, what we see about thrift shopping or buying bundle clothes was created using a mixed-method approach, which included visits to thrift stores, watching YouTube videos of thrift bloggers, reading their blogs, and obtaining newspaper interviews and feature stories about thrift shoppers and thrift shops. We can postulate that bundle mega can be regarded as a possible business of social integration, led by the grassroots or everyday-defined method to creating identity, because this is a buying act that transcends the typical social categories of socioeconomic class.